AN ANALYSIS OF THE MAIN CHARACTER OF STRUGGLING AGAINST CANCER IN THE NOVEL “THE FAULT IN OUR STARS” - Risma Yanti; Vera Kristiana (PHILOLOGY Journal of English Language and Literature, 2021)
This thesis contained an analysis of the main character's struggle against cancer in the novel entitled The fault in our stars by John Green. The method used in this research wasa qualitative method. The main objective of this research was to find out the main character's struggles against cancer in the novel The fault in our stars by Jhon Green. The results of the data analysis found 1.) What is the main character's struggles against cancer in the novel “The fault in our stars” 2.) What is the impact of the main character’sstruggles against cancer to the other characters in the novel “The fault in our stars”. Hazel's struggle against cancer that she had suffered for 3 years, by joining a support group in the heart of Jesus and meetanother cancer sufferers. Hazel Theriod had cancer at the age of 13. After Hazel joined the support group, she met people with cancer, one of them was Augustus Waters, who was never afraid of his illness. The negative impact that Hazel always felt was that she’s not a useless girl in the world.